Resolving the 1886 White Terraces riddle in the Taupō Volcanic Zone - Bunn, A. Rex (Frontiers in Earth Science, 2023)
Among the Seven Wonders of the Ancient World, only the Great Pyramid of Giza survives. Yet there is another, older than the seven, that was found and then lost again in the 19th century and once more located by the research herein: the White Terraces, named Te Tarata by indigenous peoples, of the Taupō Volcanic Zone in New Zealand. The greatest geoscience and tourist attractions in the southern hemisphere were the siliceous Pink and White Terraces. European, American, and British tourists bypassed the calcareous terraces at Saturnia, Yellowstone, and Pamukkale for the long sea voyage down to New Zealand. The 1886 Mount Tarawera eruption buried the siliceous terraces, decimating their indigenous owners and their tourism. An eruption crater lake now occupies much of the Rotomahana Basin in the Taupō Volcanic Zone, leading to assumptions that the Terraces were lost. However, no evidence was produced. The indigenous Māori owners did not believe they were lost. Controversy ensued. The resolution of this controversy is of economic and cultural importance as well as scientific interest. In 2011, a joint New Zealand-American project claimed to have found the Pink and White Terraces underwater in crater lake but produced no sinter samples. Recently, their claims were refuted. In Europe, terrestrial survey documents were unearthed, including compass bearings to the terraces by the German geologist Ferdinand Hochstetter. His survey records were digitally repatriated, and the reconstruction of his 1859 survey showed that the terrace springs lay outside the eruption crater. This renewed research in the Rotomahana Basin which has resolved the controversy. By studying topography and with the aid of Māori navigation knowledge, the geographic coordinates of the White Terraces have been triangulated and lie on land, on the shoreline outside the 1886 crater. Surprisingly, this evidence demonstrates that the White Terraces could have been located after the 1886 eruption by observation of the Rotomahana Basin with mapping available since 1864. Exploration and excavation of the Terraces are now possible. Even if degraded by the 1886 eruption, the White Terraces may earn a World Heritage listing and a second life in global tourism.